Establishment And Training Of The Covid-19 Prevention Task Force At Ypk Imanuel Pasir Putih High School, Manokwari: Pembentukan Dan Pelatihan Satgas Pencegahan Covid-19 Di Smu Ypk Imanuel Pasir Putih Manokwari - Oktoviandi Sawasemariay; Yayuk Nuryanti; Nunuk Pratiwi (Universitas Lancang Kuning, 2023)
YPK Imanuel Pasir Putih High School is an educational institution under the auspices of the Christian Education Foundation in Papua, located in Pasir Putih, Manokwari Regency, West Papua Province. There are still many active teenagers without paying attention to health protocols in the Covid-19 pandemic situation. Purpose: to form the YPK Imanuel Pasir Putih Manokwari High School Covid-19 Prevention Task Force, youth knowledge about Covid-19 prevention, explaining the importance of youth health. Methods Implementation of the training through the stages of assessment, implementation and evaluation. The training participants were 30 teenage students, BP and UKS teachers. Implementation time is three days July 28-30 2022. Results 30 youth, BP and UKS teachers understand and can demonstrate how the tasks and functions of the Covid-19 prevention task force are for youth, the simulation is carried out by each group according to the roleplay task as well as practising in the school environment every learning process, the formation of the Covid-19 Prevention Task Force. The conclusion was that a co-19 prevention task force had been formed, and youth understood the importance of health during a pandemic, implementing health protocols at YPK Imanuel Pasir Putih Manokwari High School.